Comment on: Coronavirus 2019 in Geriatrics and Long‐Term Care: The ABCDs of COVID‐19:. Issue 12 (9th September 2020) - Castagna, Alberto; Manzo, Ciro; Ruotolo, Giovanni
Abstract : This letter comments on the article by D'Adamo et al .